2019
DOI: 10.1016/j.sjbs.2019.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Efficient polysaccharides from Crinum asiaticum L.’s structural characterization and anti-tumor effect

Abstract: In this study, an efficient polysaccharide, named CAL-n (Crinum asiaticum L.-n) was isolated and purified from Crinum asiaticum L for the first time, Mw(molecular weight) of 730,000 Da. CAL-n comprised Rha(rhamnose), Sor(sorbose), Gal(galactose) and Glu(glucosein) the molar ratio of 1:61.6:1.66:4.74. The chemical structure of CAL-n was studied by Infrared spectrum and GC–MS(Gas Chromatography–Mass Spectrometer) analysis. Experimental results reflected, that the backbone of CAL-n comprised (1 → 2), (1 → 6), (1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…The cytotoxic effect of the essential oil extracted from C. asiaticum was as well established in MCF-7 cells [ 301 ]. A recent work done by Yu et al reported the inhibition of the growth of HepG 2 cells in a dose-dependent manner by polysaccharide CAL-n, an isolate from C. asiaticum [ 262 ]. Also, the neuroprotection and anti-neuroinflammatory effects in Neuronal Cell Lines were reported by Lim et al [ 279 , 302 ].…”
Section: The Genus Crinummentioning
confidence: 99%
“…The cytotoxic effect of the essential oil extracted from C. asiaticum was as well established in MCF-7 cells [ 301 ]. A recent work done by Yu et al reported the inhibition of the growth of HepG 2 cells in a dose-dependent manner by polysaccharide CAL-n, an isolate from C. asiaticum [ 262 ]. Also, the neuroprotection and anti-neuroinflammatory effects in Neuronal Cell Lines were reported by Lim et al [ 279 , 302 ].…”
Section: The Genus Crinummentioning
confidence: 99%
“…Polysaccharide is a kind of polymeric polymer compound with more than 10 monosaccharides linked by glycosidic bonds ( 10 , 11 ). Studies have shown that polysaccharides have a variety of biological activities, including improving immunity, inhibiting the proliferation and diffusion of tumor cells, and regulating blood sugar balance ( 12 14 ).…”
Section: Introductionmentioning
confidence: 99%